Case report: Two case reports of cryptogenic brain abscess caused by Fusobacterium nucleatum and literature review - Zhang, Zuoxin; Liu, Jing; Su, Linxi; Huang, Weiwei; Pei, Yuchun; Huang, Guohao; Yang, Lin; Lv, Shengqing; Yin, Jinbo; Liu, Guolong (Frontiers in Neuroscience, 2023)
Brain abscess originates from a localized cerebritis area of brain parenchyma, remaining a refractory infectious disease in the central nervous system. Causative pathogens can be wide-ranging, including bacteria, fungi, or parasites; thus, precise pathogen identification and individualized antimicrobial therapy determine patients’ outcomes. Here, we report two cases where both patients only presented with limb dysfunction, but without symptoms, signs, or biological evidence of infection. Samples were obtained through brain stereoscopic surgeries and microbial identifications were performed to confirm the infection of Fusobacterium nucleatum. Further appropriate treatments were given, and the patients recovered well. Patient 1 was a 73-year-old male with a 20-day history of left-sided limbs weakness. A brain MRI showed a space-occupying lesion with a heterogeneously ring-enhancement character in the right frontal lobe. This patient underwent puncture biopsy of the lesion with robot-assisted guidance to confirm a brain abscess. Empirical antibiotic therapy was immediately given until the pathogen was identified as Fusobacterium nucleatum; thus, he received specific antibiotic therapy with metronidazole and recovered well after treatment. Patient 2 was a 22-year-old female with heart disease history who complained of right-sided limb weakness for nine days. A brain MRI showed a circular enhanced lesion with a thin capsule wall and surrounding edema in the left frontal lobe. This patient underwent puncture drainage of the lesion with robot-assisted guidance and a brain abscess was confirmed. Empirical antibiotic therapy was given until the pathogen was identified as Fusobacterium nucleatum and then she also received metronidazole treatment. Her symptoms recovered and the lesion disappeared after 1 month. Hence, we reviewed the diagnosis and treatment of cryptogenic brain abscess caused by Fusobacterium nucleatum and highlight that precise neurosurgical interventions and identification of causative pathogens are crucial for the management of brain abscess.